Cusp Fracture Resistance of Maxillary Premolars Restored with the Bonded Amalgam Technique Using Various Luting Agents - Marchan, Shivaughn M. (Hindawi Publishing Corporation, 2009)
Objective. This in vitro study uses measurements of fracture resistance to compare maxillary premolars restored with the bonded amalgam technique using a new resin luting cement, glass ionomer, and resin-modified glass ionomer as the bonding agents. Materials. Eighty-five sound maxillary premolars were selected and randomly assigned to one of five test groups of 17 teeth each. One group of intact teeth served as the control. The remaining groups were prepared to a standard cavity form relative to the dimensions of the overall tooth and restored with amalgam alone or a bonded amalgam using one of three luting agents: RelyX Arc (a new resin luting cement), RelyX luting (a resin-modified glass ionomer), or Ketac-Cem μ (a glass ionomer) as the bonding agents. Each tooth was then subjected to compressive testing until catastrophic failure occurred. The mean loads at failure of each group were statistically compared using ANOVA with a post hoc Bonferroni test. Results. It was found that regardless of the luting cement used for the amalgam bonding technique, there was little effect on the fracture resistance of teeth. Conclusion. Cusp fracture resistance of premolars prepared with conservative MOD cavity preparations is not improved by using an amalgam-bonding technique compared to similar cavities restored with amalgam alone.